2018
DOI: 10.1590/1808-1657000892015
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of tomato plant genotypes with high foliar allelochemical contents to the leafminer Liriomyza trifolii

Abstract: The objective of this study was to assess the resistance of tomato genotypes with high foliar levels of allelochemicals to the leafminer Liriomyza trifolii. Eight tomato genotypes with contrasting levels of three different alellochemicals were tested for leafminer resistance: the TOM-687 and TOM-688 lines, which are both rich in acylsugar; ZGB-703 and ZGB-704, which are rich in zingiberene; BPX-365G-899-07-04-02 and BPX-367E-238-02, which are rich in 2-tridecanone; and 2 standard commercial hybrids (Deborah Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Tomato breeding programs focusing on in natura consumption have adopted the strategy of introgression of alleles not only for fruit traits, but also for insect resistance. Various studies have confirmed that genotypes with high allelochemical contents in the leaves, such as acylsugars and 2-tridecanone, confer resistance to whitefly and other arthropod pests (Andrade et al 2017;Oliveira et al 2012;Neiva et al 2019;Silva et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Tomato breeding programs focusing on in natura consumption have adopted the strategy of introgression of alleles not only for fruit traits, but also for insect resistance. Various studies have confirmed that genotypes with high allelochemical contents in the leaves, such as acylsugars and 2-tridecanone, confer resistance to whitefly and other arthropod pests (Andrade et al 2017;Oliveira et al 2012;Neiva et al 2019;Silva et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Programs developed in Brazil have pursued the introgression strategy of insect-resistant alleles, which are present in wild tomato species and elite inbred lines (Silva et al, 2013;Andrade et al, 2017;Vosmam et al, 2018). Pest resistance in these wild species is mediated by allelochemicals, which are generally associated with glandular foliar trichomes (Resende et al, 2006;Maluf et al, 2007;Andrade et al, 2018;Silva et al, 2018).…”
Section: Researchmentioning
confidence: 99%
“…hirsutum produces zingiberene (ZGB), a sesquiterpene hydrocarbon (Maluf et al, 2001;Freitas et al, 2002). These allelochemicals provide resistance to whitefly (B. tabaci biotype B) (Hemiptera: Aleyrodidae) (Resende et al, 2009;Silva et al, 2009;Maluf et al, 2010;Neiva et al, 2013, Andrade et al, 2017, South American tomato pinworm (Tuta absoluta) (Lepidoptera: Gelechiidae) (Goncalves Oliveira et al, 2012), mites (Tetranychus urticae and T. evansi) (Acari: Tetranychidae) (Maluf et al, 2007), leafminer (Liriomyza trifolii) (Silva et al, 2018), and aphid (Myzus persicae) (Silva et al, 2013).…”
Section: Researchmentioning
confidence: 99%
“…According to Kang et al (2009), the chemical compounds synthesised by plants may be fundamental to plant selection in leafminer species. In tomato genotypes (Solanum lycopersicum L.), the nonpreference of Liriomyza trifolii for feeding is related to high levels of allelochemicals (acylsugars, 2-tridecanone) (Silva et al 2017). In the melon, L. sativae is associated with the smaller number of trichomes and greater thickness of the leaf epidermis (de Oliveira et al, 2021).…”
Section: Introductionmentioning
confidence: 99%